(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
General (GCA) and specific (SCA) combining ability for ten quantitative characters of seven parental genotypes and 21 F1s derived from a 7x7 diallel cross without reciprocal was assessed. Combining ability analysis following Griffing,s approaches suggested the association of both additive and non-additive gene action in the genetic system with the preponderance of additive gene effect in the expression of all the traits except number of inflorescences per plant. The non-additive genetic component was exclusive or predominant for inflorescence per plant. Ranking of the parents for ten characters on GCA performance indicated that the parental genotype DS-7 was the best general combiner for pollen sterility percent, 10-green pod weight, 20-seed weight and the genotype DS-27 for the trait pod yield per plant. The estimates of SCA effect revealed that in most of the cases, combinations of high x low or even low x low exhibited high SCA effect for many characters rather than high x high cross combinations indicating the importance of gene interaction. Based on SCA performances the crosses S12 x S11 and DS-164 x DS-27 were the best specific combiners for days to 1st flowering. The crosses DS-164 x S12, DS-52 x S11, DS-164 x DS-9(t) were the best specific combinations for pollen sterility percent, pod length, and pod yield per plant respectively. DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17046